The Ambitious Kitchen cookbook : 125 ridiculously good for you, sometimes indulgent, and absolutely never boring recipes for every meal of the day - Volz, Monique (Clarkson Potter/Publishers, 2024)
"The social media star and beloved blogger behind The Ambitious Kitchen presents 125 nutrient-dense, flavor-packed recipes for every meal of the day. Monique Volz's blog, The Ambitious Kitchen, is a go-to online resource for inventive, flavorful recipes that are packed with nutrition and personality. Now in her debut book, Monique wants others to find their own Ambitious Kitchen and discover boldness, unique flavors, health, and above all, the unique happiness that food can bring to your life. Whether you're looking for a show-stopping dish to bring to a gathering, a new homecooked tradition, or a nutrient-packed meal everyone will love, The Ambitious Kitchen Cookbook has the answers. Monique joyfully showcases a balanced approach to health, with dishes that are amped up with extra vegetables, protein, and fiber next to those for when you seek comfort. Wake up and enjoy Dreamy Coffee Lover's Baked Oatmeal and The Best Cinnamon Rolls You'll Ever Eat, and if you have room for lunch: Roasted Carrot Cauliflower Salad with Sunshine Dressing and Roasty Toasty Tomato Basil Soup. Family dinner might look like Everyone's Favorite Baked Chicken Tacos or Pepperoni Pizza Baked Orzo on a busy night, or Tomato-Pesto Tie Dye Lasagna or Marry Me Ropa Vieja for a crowd. The recipes include "Make It Your Way" and "Make It Nutrient Dense" tips to customize them to your tastes. You can even make them gluten-free, dairy free, or vegan. As you turn the pages, you'll find yourself a guest at Monique's table, enjoying playful recipes that will impress everyone (including yourself!)"--